2013
DOI: 10.7324/japs.2013.38.s2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antibacterial activity and chromosome number of Algerian populations of two Chrysanthemum species

Abstract: The chemical composition of essential oil isolated from Chrysanthemum fontanesii and C. coronarium by hydrodistillation, was analysed by GC and GC/MS. A total 66 compounds representing 97.9% of the oil were identified in C. fontanesii, and 44 components representing 97.2% of the total oil in C. coronarium. The chemical composition of C. fontanesii and C. coronarium, is very different, the only common components are α-pinene, βpinene, myrcene and Δ3-carene. The Essential oil of C. fontanesii and C. coronarium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Aliphatic acids were the most abundant among nonterpene components, representing 44.4% of the total oil. Lograda et al (2013) found 41 compounds in plants collected in Algeria, being the most represented n-heneicosane (17.30%), hexadecanoic acid (12.79%), n-tricosane (10.51%), n-pentacosane (5.64%) and caryophyllene oxide (5.03%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aliphatic acids were the most abundant among nonterpene components, representing 44.4% of the total oil. Lograda et al (2013) found 41 compounds in plants collected in Algeria, being the most represented n-heneicosane (17.30%), hexadecanoic acid (12.79%), n-tricosane (10.51%), n-pentacosane (5.64%) and caryophyllene oxide (5.03%).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, C. solstitialis may be used as an antibiotic for S. aureus infections ( Tekeli et al, 2011 ). Lograda et al (2013) tested the biological activity of the essential oil of C . solstitialis grown in Algeria against nine bacterial strains, and it showed moderate to significant antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison with previous works relative to Algerian R. officinalis, cineole-rich essential oils have been reported from plants harvested in Bordj Bou Arreridj (South-East Algiers), [7,26] Béjaïa and Tébessa (Eastern Algeria), [26,28] El-Bayadh, [21,29] Khenchela. [30] Camphor-rich EOs have been isolated from plants collected in Batna and M'Sila, [26] Constantine (North-East Algeria), [36] Djelfa and Laghouat. [23] R. officinalis oil samples containing fair amount of verbenone have been reported from plants harvested near Algiers, wild or cultivated, [23,27,35] Annaba, (Wild) [11] Sétif, (cultivated) [12] (Eastern Algeria), Tlemcen, (cultivated), [24] and overall, Mascara, (Western Algeria).…”
Section: Chemical Variability Of R Officinalis From Algerian Saharamentioning
confidence: 94%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] A few papers concerned 2-6 oil samples. [23,[24][25][26][27][28][29][30] Lastly, a study investigated the composition of 15 oil samples, however no statistical analysis was performed. [31] Otherwise, various studies concerned the composition as a function of the plant life cycle, [32] and the isolation of rosemary oils by different processes.…”
Section: Introductionmentioning
confidence: 99%